(3eSGgeI dhMI GdbjGOI GdGLJeGYjI aj JQTjO GJNGP bQGQJ GdGOGQI GdQjGVjI (B: (3OQGSI ejOGfjI Ydi eSJhi eOjQjGJ GdTHGH h GdQjGVI dhdGjI GdLRGFQ s - (3HdMfjT , GSeGYjds; (3MOGH, Sdjes; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3eY JRGjO JYbO GdeTcdGJ GdEOGQjI JYbOJ eYgG YedjI GJNGP GdbQGQGJ GdJj JSGge aj MdgG hef HjfgG bQGQGJ EOGQI GdehGQO GdHTQjI, hgj GdeJYdbI CSGSG HGNJjGQ CaVd GdSHd dJSjjQ CYeGd GdEOGQI GdQjGVjI aj GdeSJbHd, hWGdeG cGf GdeSJbHd jJSe HOQLGJ eJaGhJI ef YOe GdJCcO aEf GJNGP GdbQGQGJ GdQTjOI jJWdH bGYOI ef GdeYdheGJ GdMbjbjI Yf GdeGVj hGdMGVQ MjK JSJNOe EOGQI GdehGQO GdHTQjI Jdc GdeYdheGJ aj GNJjGQ CaVd HOGFd GdYed HGdTcd GdPj jecfgG ef Jbdjd BKGQ MGdI YOe GdJCcO GdSGFOI aj GdHjFI GdeMjWI HgG, hJQTjO GdcKjQ ef GdbQGQGJ GdeJYdbI HEOGQI GdehGQO GdHTQjI, eeG jJWdH ef GdEOGQI GdQjGVjI GdMjGRI Ydi dhMI bjGOI HeG JMJhjg ef eDTQGJ JOd Ydi WHjYI GdbQGQ GdhGLH GJNGPg(B.s
(3OcJhQGIs
Keywords: (3GdGOGQI GdQjGVjIs; (3GdGOGQI h GdJSjjQ GdQjGVjs